IMPACT OF COUNSELING ON IMPROVING ADHERENCE TO DYSLIPIDEMIA PATIENT - Rangkuti, Saru Noliqo; Nasution, Azizah; Khairunnisa, Khairunnisa (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to determine the impact of counseling on adherence of dyslipidemia outpatients to the prescribed medications in An-Nisa Hospital Tangerang period July 2016–November 2016. Methods: This prospective a quasi-experimental design with pre- and post-test design was done to analyze the impact of counseling in An-Nisa Hospital Tangerang. Patients' characteristics were statistically analyzed using Chi-square. The patient adherence toward therapy was analyzed using Morisky Medication adherence scale-8. Results: The present study indicated that most of the patients (70%) were females with ages: ˃50.70%; ≤50.30%. The counseling significantly affected the adherence level on dyslipidemia patients, p<0.001. Conclusion: This research proved that counseling had a positive impact on the patients' adherence.